EARLY RETIREMENT PROGRAM MODEL WITH SHARIA PRINCIPLES USING ACCRUED BENEFIT COST METHOD - Zulkatri, Eli
This study aims to simulate the process of Early Retirement Funding with Sharia principles. The actuarial calculation applies the Accrued Benefit Cost method consisting of Unit Credit and Project Unit Credit to determine the amount of participant benefits, normal cost and actuarial liability. This study also calculates the benefits of early retirement participants with funds developed in several choices of Islamic investment packages adopted from the investment packages of Islamic Financial Institutions and Stocks Pension Funds. This research approach is quantitative with some actuarial assumptions to be applied to a Sharia insurance company in Jakarta. In the calculation simulation results, it is found that the total normal cost of participants under the Unit Credit method is always greater than the Project Unit Credit, but the normal cost to the Project Unit Credit will always be greater at the beginning of the working period compared to the Unit Credit. Meanwhile, in actuarial liabilities, the Project Unit Credit will generate a larger actuarial liability than the Credit Unit. In development funds, investment options with a larger portion of development funds being developed in Islamic stock instruments will generate greater benefits compared to other investment package options in this research.